A cross-sectional study of parental awareness of and reasons for lack of health insurance among minority children, and the impact on health, access to care, and unmet needs. Issue 1 (December 2016) - Flores, Glenn; Lin, Hua; Walker, Candy; Lee, Michael; Portillo, Alberto; Henry, Monica; Fierro, Marco; Massey, Kenneth
Abstract Background Minority children have the highest US uninsurance rates; Latino and African-American children account for 53 % of uninsured American children, despite comprising only 48 % of the total US child population. The study aim was to examine parental awareness of and the reasons for lacking health insurance in Medicaid/CHIP-eligible minority children, and the impact of the children's uninsurance on health, access to care, unmet needs, and family financial burden. Methods For this cross-sectional study, a consecutive series of uninsured, Medicaid/CHIP-eligible Latino and African-American children was recruited at 97 urban Texas community sites, including supermarkets, health fairs, and schools. Measures/outcomes were assessed using validated instruments, and included sociodemographic characteristics, uninsurance duration, reasons for the child being uninsured, health status, special healthcare needs, access to medical and dental care, unmet needs, use of health services, quality of care, satisfaction with care, out-of-pocket costs of care, and financial burden. Results The mean time uninsured for the 267 participants was 14 months; 5 % had never been insured. The most common reason for insurance loss was expired and never reapplied (30 %), and for never being insured, high insurance costs. Only 49 % of parents were aware that their uninsured child was Medicaid/CHIP eligible. Thirty-eight percent of children had suboptimal health, and 2/3 had special healthcare needs, but 64 % have no primary-care provider; 83 % of parents worry about their child's health more than others. Unmet healthcare needs include: healthcare, 73 %; mental healthcare, 70 %; mobility aids/devices, 67 %; dental, 61 %; specialty care, 57 %; and vision, 46 %. Due to the child's health, 35 % of parents had financial problems, 23 % cut work hours, and 10 % ceased work. Higher proportions of Latinos lack primary-care providers, and higher proportions of African-Americans experience family financial burden. Conclusions Half of parents of uninsured minority children are unaware that their children are Medicaid/CHIP-eligible. These uninsured children have suboptimal health, impaired access to care, and major unmet needs. The child's health causes considerable family financial burden, and one in 10 parents ceased work. The study findings indicate urgent needs for better parental education about Medicaid/CHIP, and for improved Medicaid/CHIP outreach and enrollment.